Open Publishing Student Research Projects: A Conversation and Reflection - Vanner, Catherine; Cormier, Dave (Journal of Teaching and Learning, 2025)
This reflective article describes an initiative that created a publicly accessible e-book comprised of digital media (podcast, video, web essay) research assignments produced by Bachelor of Education students at a Canadian university. A teacher- education instructor and a learning specialist designed and undertook the project collaboratively. The article is written as a conversation that moves between our two perspectives on the project. We share the project as an innovative model that encourages students, particularly suited for those in professional programs or graduate studies, to produce assignments that contribute to the scholarly body of knowledge on a given subject.